Investigating pedagogical practices of English First Additional Language educators in Grade 12 short stories: a case study - Jabe, Sizwe (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa)
The focus of this study was to investigate pedagogical practices of English First Additional Language educators in teaching Grade 12 short stories. An interpretive qualitative case study of three educators from three high schools in Chris Hani West district, in Eastern Cape were purposefully selected. Lesson observations, semi-structured interviews, and document analysis (lesson plans) with three English FAL educators were used to collect data. Shulman's (1986) Pedagogical Content Knowledge was used as the theoretical framework and analytical tool for the study. Data revealed ineffective teaching strategies and on-the-surface subject matter knowledge that hampers the critical teaching of short stories. It also showed that educators have limited knowledge of learners' learning difficulties and how to address them. The study recommends less teacher talk that was observed in many classes, to be replaced by extended discussions on the part of the learners. Educators should establish a variety of contemporary teaching strategies which put critical thinking and active learning before examination preparation. Lastly, educators, in their teaching of short stories, should consult various resources and attend content workshops to keep subject knowledge up to date.
Keywords: Short stories-- Study and teaching (Secondary) -- South Africa -- Eastern Cape; Pedagogical content knowledge; English-medium instruction -- South Africa -- Eastern Cape; Teacher effectiveness -- South Africa -- Eastern Cape; Educational change -- South Africa -- Eastern Cape